The dual role of IL-17 in periodontitis regulating immunity and bone homeostasis - Tang, Zhongyuan; Jin, Lijian; Yang, Yanqi (Frontiers in Immunology, 2025)
Periodontitis is a common dysbiotic bacteria-induced inflammatory disease characterized by alveolar bone resorption, leading to tooth loss. Interleukin-17 (IL-17) is a critical cytokine with dual roles in periodontium, which exerts the function of host defense, including neutrophil recruitment, phagocytosis, and mucosal immunity. However, excessive expression of IL-17 causes persistent chronic inflammation, local tissue breakdown, and bone loss. This review highlights the protective and pathological functions of IL-17 on immunity and bone homeostasis in inflammatory bone-related diseases. We also provide the latest findings with IL-17 knockout mice in periodontitis and highlight complex immune responses under various experimental models. This may provide a critical perception of inflammatory bone-related disease management using an immune-modulating strategy.